2010
DOI: 10.1183/09031936.00165409
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in COPD in five Latin American cities: the PLATINO study

Abstract: There is evidence to suggest sex differences exists in chronic obstructive pulmonary disease (COPD) clinical expression. We investigated sex differences in health status perception, dyspnoea and physical activity, and factors that explain these differences using an epidemiological sample of subjects with and without COPD.PLATINO is a cross-sectional, population-based study. We defined COPD as post-bronchodilator forced expiratory volume in 1 s/forced vital capacity ratio ,0.70, and evaluated health status perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
55
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(71 citation statements)
references
References 37 publications
12
55
1
3
Order By: Relevance
“…Our results show a signifi cant association between patient's age and COPD prevalence in a spirometrybased data set (4,(37)(38)(39), and further point out the statistically signifi cant diff erences between spirometry and non-spirometry data, among which spirometry-based estimates generally appear more homogenous and internally consistent.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Our results show a signifi cant association between patient's age and COPD prevalence in a spirometrybased data set (4,(37)(38)(39), and further point out the statistically signifi cant diff erences between spirometry and non-spirometry data, among which spirometry-based estimates generally appear more homogenous and internally consistent.…”
Section: Discussionmentioning
confidence: 68%
“…Th e limited amount of published research in Africa may be due to challenges in conducting studies that would fully adhere to internationally agreed case defi nitions (40). For example, many studies now use post-bronchodilatory spirometry as a gold standard (42); whereas others state that using post-brochodilator estimates may result in a 5-50% reduction in prevalence compared to prebronchodilator values (39). It has been suggested that the low research output refl ects the poor recent availability of research funding for COPD by funding agencies, which in turn refl ects their lack of priority given to COPD (11,16).…”
Section: Public Health Response To Copd In Africamentioning
confidence: 96%
“…Secondly, the subjects recruited in the present study were all males. Although Lopez Varela et al [32] reported that women with COPD showed greater physical limitations than men, Torres et al [33] reported that gender differences in skeletal muscle characteristics were not found in COPD patients. The importance of the validation study, however, is the difference between the absolute activity and the measured activity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the prevalence of COPD among men was consistently higher than in women across all world regions, settings and income categories. Some authors question the independent etiological role of gender in the development of COPD [166], given that the risk profile among men favours the development of disease. Recent reviews suggested that increased tobacco use among women in high-income countries and the higher risk of exposure to indoor air pollution (such as biomass fuels used for cooking and heating) in low-and middle income countries may contribute to reducing gender differences in COPD in future [1].…”
Section: Discussionmentioning
confidence: 99%